(untitled) (Research, Society and Development, 2020)
This review aimed to evaluate the effect of magnesium supplementation on performance parameters in athletes. The bibliographic survey was performed in the Pubmed, Cochrane and Science Direct databases, using the keywords “magnesium”, “supplementation”, “performance” and “exercise”. Clinical trials conducted were found to supplement magnesium between 10 and 900 mg / day. The duration of interventions ranged from one week to 12 weeks. To evaluate performance and performance were determined: lactate level, DNA damage, adrenocorticotropic hormone secretion, cortisol and testosterone, as well as measuring strength, isometry, distance traveled, time and blood pressure. The relationship between magnesium and performance in particular is still poorly studied due to inconsistent scientific data recommending an adequate dose according to sport, however, evidence suggests that magnesium may improve performance parameters, but should Keep in mind that magnesium supplementation should be tailored to the individual’s daily dietary intake.